2012
DOI: 10.1088/2041-8205/761/1/l2
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogen in NGC 1851 Red Giant Branch and Asymptotic Giant Branch Stars: Quadrimodal Distributions

Abstract: The Galactic globular cluster NGC 1851 has raised much interest since Hubble Space Telescope photometry revealed that it hosts a double subgiant branch. Here we report on our homogeneous study into the cyanogen (CN) band strengths in the red giant branch (RGB) population (17 stars) and asymptotic giant branch (AGB) population (21 stars) using AAOmega/2dF spectra with R ∼ 3000. We discover that NGC 1851 hosts a quadrimodal distribution of CN band strengths in its RGB and AGB populations. This result supports th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 37 publications
(69 reference statements)
9
50
0
Order By: Relevance
“…In our study, we presented the first spectroscopic derivation of N abundances of giants in this cluster made for such a large number of stars on the RGB, which nicely supports the results by Villanova et al (2010) and Campbell et al (2012) based on much more limited samples. While we cannot state anything on the total C+N+O sum with not knowing the C abundance of the individual objects, we are able to spectroscopically ascertain that stars are located on the redder sequence in NGC 1851 because they are N-rich.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…In our study, we presented the first spectroscopic derivation of N abundances of giants in this cluster made for such a large number of stars on the RGB, which nicely supports the results by Villanova et al (2010) and Campbell et al (2012) based on much more limited samples. While we cannot state anything on the total C+N+O sum with not knowing the C abundance of the individual objects, we are able to spectroscopically ascertain that stars are located on the redder sequence in NGC 1851 because they are N-rich.…”
Section: Resultssupporting
confidence: 83%
“…There are six stars in common between our analysis and the sample of 17 RGB stars analyzed by Campbell et al (2012). Using the Strömgren photometry available to us for these 6 objects, we see that the two stars with the highest values of δS(3839) (stars 41113 and 32112 in Table 1 of Campbell et al 2012) lie on the redder RGB sequence.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…of AGB stars have indicated that they may be populated exclusively by Na-poor objects (Campbell et al 2013). Furthermore, the RGB and AGB populations in NGC 1851 exhibit a complex distribution in CN molecular line strengths (Campbell et al 2012). Therefore, we were also interested in studying the CNO content of AGB stars in NGC 1851.…”
Section: Sample Selection and Observationsmentioning
confidence: 99%